2012
DOI: 10.1016/j.jtcvs.2012.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Experience with the first 50 ex vivo lung perfusions in clinical transplantation

Abstract: Transplantation of high-risk donor lungs after 4 to 6 hours of ex vivo lung perfusion is safe, and outcomes are similar to those of conventional transplants. Ex vivo lung perfusion improved our center use of donor lungs, accounting for 20% of our current lung transplant activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
212
0
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 271 publications
(230 citation statements)
references
References 29 publications
12
212
0
6
Order By: Relevance
“…Subsequently, indications of high-risk DCDD donor lungs that required EVLP included any of the following: (1) last PaO 2 /FiO 2 (P/F) < than 300 mmHg; (2) pulmonary edema detected on chest X-ray or during examination of the lungs at procurement; (3) poor lung compliance during examination of the lungs at procurement; (4) high-risk history (e.g. multiple blood transfusions, questionable history of aspiration) (16,17); (5) interval between WLST and arrest >60 minutes.…”
Section: Donor Selectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Subsequently, indications of high-risk DCDD donor lungs that required EVLP included any of the following: (1) last PaO 2 /FiO 2 (P/F) < than 300 mmHg; (2) pulmonary edema detected on chest X-ray or during examination of the lungs at procurement; (3) poor lung compliance during examination of the lungs at procurement; (4) high-risk history (e.g. multiple blood transfusions, questionable history of aspiration) (16,17); (5) interval between WLST and arrest >60 minutes.…”
Section: Donor Selectionmentioning
confidence: 99%
“…Additionally, there should be no worsening x-ray infiltrate and no purulent/frothy secretions on the interval bronchoscopy as well (17).…”
Section: Ex Vivo Lung Perfusion (Evlp)mentioning
confidence: 99%
See 1 more Smart Citation
“…As a significant nonclassical monocyte population was discovered in this study, it is likely that the benefits observed posttransplant will be conferred in human EVLP. Early clinical trial data have indicated equivalence in clinical outcome between standard transplant and EVLP reconditioned lungs, allowing an expanded donor organ pool (20)(21)(22)(23). Although significantly beneficial in itself, there is scope for further improvements in clinical outcome with EVLP via modulation of the donor leukocyte repertoire.…”
Section: Stone Et Almentioning
confidence: 99%
“…Other therapies such as steroids treatment with methylprednisolone are commonly used in EVLP but their effect on outcomes is still unclear [80,81]. An adenosine A2A agonist has also been shown to improve lung funcion during EVLP [82].…”
Section: J Ventilation and Perfusion Strategies In Evlpmentioning
confidence: 99%